Detection of Increased Plasma Interleukin-6 Levels and Prevalence of Prevotella copri and Bacteroides vulgatus in the Feces of Type 2 Diabetes Patients - Leite, Aline Zazeri; Rodrigues, Nathália de Campos; Gonzaga, Marina Ignácio; Paiolo, João Carlos Cicogna; de Souza, Carolina Arantes; Stefanutto, Nadine Aparecida Vicentini; Omori, Wellington Pine; Pinheiro, Daniel Guariz; Brisotti, João Luiz; Matheucci Junior, Euclides; Mariano, Vânia Sammartino; de Oliveira, Gislane Lelis Vilela (Frontiers in Immunology, 2017)
Intestinal dysbiosis and metabolic endotoxemia has been associated with metabolic disorders, such as obesity, insulin resistance and type 2 diabetes (T2D). The main goal of the present study was to evaluate the intestinal dysbiosis in Brazilian T2D patients and correlate these data with inflammatory cytokines and lipopolysaccharides (LPS) plasma concentrations. This study was approved by the Ethics Committees from Barretos Cancer Hospital and all individuals signed the informed consent form. Stool samples were required for DNA extraction, and the V3/V4 regions of bacterial 16S were sequenced using an Illumina platform. Peripheral blood were used to quantify inflammatory cytokines and plasma LPS concentrations, by CBA flex and ELISA, respectively. Statistical analyses were performed using Mann-Whitney and Spearman’s tests. Analysis of variance, diversity indexes and analysis of alpha and beta-diversity were conducted using an annotated OTU table. This study included 20 patients and 22 controls. We observed significant differences (P<0.01) in the microbiota composition (beta-diversity) between patients and controls, suggesting intestinal dysbiosis in Brazilian T2D patients. The prevalent species found in patients’ feces were the gram-negatives Prevotella copri, Bacteroides vulgatus, Bacteroides rodentium, and Bacteroides xylanisolvens. The proinflammatory interleukin-6 (IL-6) was significantly increased (P<0.05) in patients’ plasma and LPS levels were decreased. We find correlations between the proinflammatory interferon-gamma (IFN-γ) with gram-negatives Bacteroides and Prevotella species, and a positive correlation between the LPS levels and Prevotella copri reads. The Prevotella copri and Bacteroides vulgatus species were associated with insulin resistance in previous studies. In this study, we suggested that the prevalence of gram-negative species in the gut and the increased plasma IL-6 in patients could be linked to low-grade inflammation and insulin resistance. In conclusion, the Prevotella copri and Bacteroides vulgatus species could represent an intestinal microbiota signature, associated with T2D development. Furthermore, the identification of these gram-negative bacteria, and the detection of inflammatory markers, such as increased IL-6, could be used as diabetes predictive markers in overweight, obese and in genetically predisposed individuals to develop T2D.